The Catholic reception of continental philosophy in North America - Floyd, Gregory P., 1984-; Rumpza, Stephanie, 1986- (University of Toronto Press, 2020)
"Why is it that so many Catholics continue to find Continental Philosophy attractive? This volume by leading philosophers and theologians explores the reception of continental philosophy, and its history within Catholic Institutions in the twentieth century. From its earliest days in North America, Catholic philosophers and theologians have been the strongest supporters of continental philosophy; in turn, this has contributed to the intellectual enrichment of Catholic universities, making an important mark on Catholic thought. By taking a stance towards the evolving relationship between Catholics and Continental Philosophy, many of the contributors to this volume serve as living demonstrations that this engagement is far from over. Exploring the mutual interests that made this alliance possible as well as their underlying tensions, contributors provide, for the first time, a sustained account of the historical, institutional, and intellectual relationship between Catholicism and Continental Philosophy."--